2021
DOI: 10.3892/ol.2021.12567
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SIRT1 to inhibit the proliferation of multiple myeloma cells

Abstract: Multiple myeloma (MM) is the second most common hematopoietic malignancy and remains an incurable disease. Thus, novel drugs and therapeutic methods are required for patients with MM. The present study aimed to investigate the effect of sirtuin 1 (SIRT1) inhibitor cambinol on the proliferation and apoptosis of myeloma cell lines, RPMI8226 and U266. Moreover, the present study evaluated the underlying molecular mechanisms of proliferation inhibition and apoptosis induced by cambinol. A Cell Counting Kit-8 assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The idea of treating BC patients with new active agents capable to re-establish expression of tumor suppressor genes, which are silenced by epigenetic mechanisms is being tested [67]. HDIs seem to be a promising group of anticancer drugs, particularly in combination with other anticancer agents [84,208] or radiotherapy [209,210]. So far, 4 HDIs have been approved by the US FDA for the treatment of certain types of hematological malignancy [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of treating BC patients with new active agents capable to re-establish expression of tumor suppressor genes, which are silenced by epigenetic mechanisms is being tested [67]. HDIs seem to be a promising group of anticancer drugs, particularly in combination with other anticancer agents [84,208] or radiotherapy [209,210]. So far, 4 HDIs have been approved by the US FDA for the treatment of certain types of hematological malignancy [67].…”
Section: Discussionmentioning
confidence: 99%
“…No sirtuin inhibitors have been approved by FDA so far. Preclinical studies indicate that some sirtuin inhibitors show promising in vitro results used alone against solid tumors [ 83 , 84 , 85 , 86 , 87 ]; however, the data obtained from combined-treatment research are controversial, concluding different types of pharmacological interactions between tested drugs [ 88 , 89 , 90 , 91 ].…”
Section: Histone Deacetylase Inhibitors (Hdis)mentioning
confidence: 99%
“…However, it has been shown that HDACs and SIRTs could deacetylate and other non-histone substrates modifying their action. Therefore, the targets of HDACs become important key-players in cellular biology with multiple functions and mode of action and consequently, the HDACs a very promising therapeutic strategy in multiple myeloma [ 33 , 36 , 115 , 116 ]. Some of the different functions of HDAC inhibitors in cancer are depicted in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In NCI-H460 lung cancer and HeLa cervical cancer cells, Cambinol increased acetylation levels of several sirtuin substrates, including p53, α-tubulin, FOXO3a, and Ku70 ( Heltweg et al, 2006 ). In RPMI8226 and U266 multiple myeloma cells, Cambinol induced apoptosis, cell proliferation impairment, and cell cycle arrest by increasing p53, p21, cleaved PARP, and cleaved caspase 3 ( Lu et al, 2021 ). In orthopedic tumor xenograft mice model with HepG2 hepatocarcinoma cells, Cambinol significantly reduced tumor growth, which was consistent with the SIRT1 knockdown results of in vivo intrahepatic xenograft mouse model ( Portmann et al, 2013 ).…”
Section: Sirtuin Modulators In Cancermentioning
confidence: 99%
“…- (Heltweg et al, 2006;Marshall et al, 2011;Portmann et al, 2013;Ceballos et al, 2021;Lu et al, (Grozinger et al, 2001;Mai et al, 2005;Ota et al, 2006;Kojima et al, 2008;Kozako et al, 2012;Fong et al, 2014;Zhou et al, 2014;Safari et al, 2017;Ma et al, 2018) -H1299 non-small lung and HeLa cervical: decreased cell proliferation (Lain et al, 2008;McCarthy et al, 2012;Dai et al, 2016;Spiegelman et al, 2018;Lee et al, 2019 or quercetin activated sirtuins (Aksoy et al, 2006;Lee, 2006;Escande et al, 2013). Because this review specifically summarizes modulators that directly bind to sirtuins, we will not explain these indirect modulators in detail.…”
Section: Kpm-2mentioning
confidence: 99%